Makna Simbolik dalam Teks Dhammapada: Kajian Semantik Untuk Pendidikan Budi Pekerti Umat Buddha - Hendri Hendri; Santi Paramita (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This study examines the symbolic meanings in the Dhammapada text through a simple semantic approach. Many Buddhists understand the Dhammapada only literally, without exploring the deeper symbolic meanings intended to transform character and behavior. This research uses a descriptive qualitative method by analyzing ten selected verses from the Dhammapada, comparing their literal meanings (denotative) with symbolic meanings (connotative). The findings show that each verse in the Dhammapada contains moral wisdom that can be applied in daily life. For example, the metaphor of light represents wisdom, darkness represents ignorance, and the middle path represents balance in life. These findings have practical implications for Buddhist character education, where understanding symbolic meanings helps students internalize moral values more deeply than merely memorizing texts.